THE SEMIOTIC ANALYSIS OF POSTERS AGAINST DOMESTIC VIOLENCE IN JORDAN: Received: 29th September 2021; Revised: 07th January 2022, 13th March 2022; Accepted: 22nd March 2022 - Altamimi, Rasha Salhab (PEOPLE: International Journal of Social Sciences, 2022)
This paper aims to define the role of the communication posters designed by feminist protesters in expressing the rejection of domestic violence against women in Jordan, since few studies address such topics. In response to a notorious incident in 2019 where a suburban woman in Jordan was physically abused by her husband in front of her children, Jordanian feminists staged a protest march in the heart of the capital city, Amman. The victim became permanently disabled due to this violence. Several female protesters joined the demonstration, carrying reflective visual and verbal posters to show their empathy towards the victim and repudiation of the victimization. Moreover, these posters have been circulated via Twitter, with users writing empathic comments on the images and using several hashtags such as #Jerash Crime and #Enough, which prove that these posters are effective in vindicating women's rights, besides claiming security and protection against violence. The research methodology involved conducting a semiotic analysis on the most explicit posters raised during the march and distributed via Twitter to show condemnation of the brutal physical violence against the Jordanian victim.